Millennial Generation Behavior in Halal Tourism in South Sulawesi - Nurul Huda; Nova Rini; Muslikh Muslikh (Journal of Indonesian Tourism and Development Studies, 2022)
The halal industry is currently the main focus in developing the sharia economy. One that is related to the halal industry is halal tourism. Thus, this article aims to look at the role of the millennial generation in buying halal tourism in the South Sulawesi region. The research method used is quantitative. The analytical method used is the Path Analysis method with SmartPLS 3.0 software. The method of data collection is by purposive sampling technique. The number of respondents is 181. This study showed that the variable of Islamic religiosity has a significant effect on millennial attitudes and behavior in purchasing halal tourism. While the halal tourism knowledge variable in this study had a significant effect on the attitude variable, it did not significantly affect their behavior. The Islamic Religious Millennial Generation has a significant effect on the attitude of purchasing halal tourism. Millennials and Islamic Religious Attitude have a considerable influence on the buying behavior of halal tourism.Keywords: Attitude, Behavior, Halal Tourism, Islamic Religiosity, Millennial Generation.